Mortality in Common (Sterna hirundo) and Sandwich (Thalasseus sandvicensis) Terns Associated with Bisgaard Taxon 40 Infection on Marco Island, Florida, USA. (April 2021) - Niedringhaus, Kevin D.; Shender, Lisa A.; DiNuovo, Adam; Flewelling, Leanne J.; Maboni, Grazieli; Sanchez, Susan; Deitschel, P.J.; Fitzgerald, Joanna; Nemeth, Nicole M.
Summary: Widely distributed aquatic species such as terns are highly dependent on, and can serve as indicators of, the global health of marine and other aquatic environments. Documented mass mortality events in terns have been associated with anthropogenic, weather-related and, less commonly, infectious causes. This study describes a multispecies mortality event associated with brevetoxicosis and Bisgaard taxon 40-induced sepsis involving common ( Sterna hirundo ) and sandwich ( Thalasseus sandvicensis ) terns off the southwest coast of Florida, USA, in November and December 2018. During an approximately 6–8-week period, a large number of birds were found dead or displayed weakness, ataxia or other neurological signs. Many were admitted to a wildlife hospital for evaluation, but most died or were euthanized due to poor prognosis. Necropsy of 12 birds revealed minimal or non-specific gross lesions. Initial toxicology screening of tissues for brevetoxins revealed levels that could be consistent with brevetoxicosis. However, histology revealed multiorgan inflammation and necrosis associated with a gram-negative bacillus. A bacterium isolated on aerobic culture of liver and heart tissues was unidentifiable in the MALDI-TOF database. Subsequently, 16 S rRNA gene sequencing revealed that the isolate shared 99.33% homology with Bisgaard taxon 40 from the Pasteurellaceae family. While the source of the bacterium and potential association with brevetoxin exposure are unclear, histopathology suggests that the bacterium was the proximate cause of clinical signs and mortality in all birds examined as well as the scale of the mortality event. This report highlights the need to conduct detailed investigations into wildlife mortality events and expands on the current, limited knowledge of the effects of novel Pasteurellaceae bacteria on avian health. Graphical abstract: Image 1